Electrodeposition of Ni-TiAlN Nanocomposite Coating For Wear and Corrosion Protection: A Review - Budi, Esmar; Nasbey, Hadi; Budi, Agus Setyo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2013)
Development of nanocomposite thin coating has improved the wear and corrosion resistance of materials. Hard nano particles such as SiC, TiC and TiN was electrodeposited on metal or alloy matrix such as Ni to form a hard nanocomposite thin coating. However, the development of Ni-TiAlN nanocomposite coating by using electrodeposition for wear and corrosion protection is still lack of reports. TiAlN is a transition metal nitride with mechanical and corrosion protection, especially at high temperature operation. This compound is widely used in technology applications such as diffusion barrier of electronic components and hard coating on cutting tools. One of methods to fabricate the nanocomposite coating is electrodeposition since it is easy, low cost and high rate production. This paper is aimed to review on the development of Ni-TiAlN nanocomposite coating by using electrodeposition for wear and corrosion protection. Keywords: Ni-TiAlN nanocomposite coating, electrodeposition, wear, corrosion.